Efeitos do programa “Melhoria da educação” sobre o processo formativo docente em uma unidade escolar do município de Suzano - Battani, Rafael Artur (2022)
Considering that teacher training is a process of continuous reflection and it takes place in the midst of the complexity of different times and contexts to make the individual aware, above all, with regard to their training process (García, 1999), this study focused on the goal of carrying out a research in a Municipal Elementary School (EMEF) in the city of Suzano to investigate the effects of "Improvements in Education" on the refinement of training guidelines proposed by the pedagogical coordination to teachers of a school in the city and will identify the perception of the teachers and the pedagogical coordinator about the possible effects of the program on their training process. Therefore, the methodology used to support the research will be qualitative analysis, which will be structured through information produced from data collection with interviews and document analysis. The interviews will take place with five subjects and the research instrument will consist of a script of five open-ended questions that will be performed at the school institution in an environment and time to be determined. Three guidelines will be raised that directed the Collective Pedagogical Work Schedule before the implementation of the program and three after it, to be analyzed. As for the treatment of the information collected, content analysis based on Bardin (2016) will be used, which will observe the data of the conducted research and highlight the steps to be followed to make the scientific treatment of the information. As a way of discussing the results, based on the floating reading of the collected data and based on the elements of expressiveness and representativeness, some terms were listed that, in some way, were associated with the pedagogical work guidelines. The results presented led us to consider, at the end of the study, that it was urgent to enable a more careful look at the processes of teacher training and even more attentive to the importance of the active participation of teachers in choosing what is considered a focus of study and deepening your practice